Stability of weathered cut slope by using kinematic analysis - Haryati, Awang; Ahmad Faiz, Salmanfarsi; M S, Aminudin; Mohamad Idris, Ali (IOP Publishing Ltd, 2021)
Rock slope engineering involves the designing of safe and stable rock slopes for a certain lifespan. Different rock slopes exhibit different strengths of material that reacts differently to external forces. Rock strength can decrease over time due to weathering process. In addition, the presence of discontinuity can lead to structurally controlled slope failure. The study focuses on a large exposed rock slope in Sri Jaya area, where the exposed granitic rock was cut by several sets of discontinuities. In addition to the discontinuities, the slope exhibited several weathering grades. The objective of this study is to map the weathering and discontinuity of the rock slope, in order to determine the stability of the slope. Schmidt rebound hammer tests were carried out to determine the extent of the weathering grade of the slope material. The collected field data were then analysed using the kinematic analysis to determine potential mode(s) of failure. From the analysis, it is predicted that there is significant percentage for toppling failure and wedge failure to occur in the weathered rock material.